Factors Associated With Requests for Mental Health Services Among Sexual Violence Survivors in South Korea: A Retrospective Cohort Study - Bokyung Choi; Myung Kyung Lee (Journal of Forensic Nursing, 2026)
Background Although Sunflower Centers in South Korea facilitates access to care through an integrated support model, the specific survivor and incident characteristics associated with requests for mental health services remain poorly understood. Aim To identify factors associated with requests for mental health services among sexual violence survivors at a SunFlower Center in South Korea. Methods Retrospective cohort study of 269 cases from the Sunflower Center between July 2020 and December 2022. Results Overall, 41.3% of survivors requested mental health services. Among minor survivors, intact memory of the incident was associated with a higher likelihood of requesting mental health services [odds ratio ( OR ): 6.44, 95% CI: 1.05–39.54]. Among adult survivors, assault by a socially acquainted person ( OR : 4.13, 95% CI: 1.17–14.55) or a chat partner ( OR : 4.10, 95% CI: 1.13–14.93) was associated with a higher likelihood of requesting therapy. Conversely, genital penetration was associated with a lower likelihood of requesting psychotherapy ( OR : 0.33, 95% CI: .14–.79). Conclusion These findings highlight the importance of age-sensitive, trauma-informed care. Forensic nurses play a key role in coordinating mental health referrals based on survivor and assault characteristics.